[OP.4A.02] SHORT TERM BLOOD PRESSURE VARIABILTY AS PREDICTOR OF FUTURE EVENTS IN YOUNG STAGE I HYPERTENSIVES. (September 2016) - Saladini, F.; Mos, L.; Fania, C.; Benetti, E.; Mazzer, A.; Cozzio, S.; Bortolazzi, A.; Garavelli, G.; Casiglia, E.; Palatini, P.
Abstract : Objective: The association of short-term blood pressure variability (BPV) with cardiovascular events is controversial. Aim of this study was to investigate whether BPV is associated with poorer outcome in the HARVEST, a prospective cohort study of non-diabetic subjects screened for stage 1 hypertension. Design and method: We performed 24-hour ambulatory blood pressure monitoring in 1204 participants aged 33.1 ± 8.5 years with a follow-up duration of at least 6 months. All were untreated at baseline examination. Median follow-up was 12.6 years. Hazard ratios for weighted 24-hour blood pressure standard deviation were computed, adjusting for mean 24-hour blood pressure, age, sex, body mass index, smoking, alcohol and coffee consumption, physical activity habits, parental cardiovascular disease, total cholesterol, and development of hypertension needing treatment during the follow-up. Results: Standard deviation of 24-hour systolic blood pressure (SSD) was unrelated to age and sex and was associated with mean 24-hour systolic blood pressure (p < 0.001) and smoking (p = 0.001). Standard deviation of 24-hour diastolic blood pressure (DSD) was associated with male sex (p = 0.02), younger age (p = 0.005), mean 24-hour diastolic blood pressure (p = 0.007) and body mass index (p = 0.01). During the follow-up 74 hard end-points were observed. In a parsimonious multivariable Cox model, 24-hour SSD (p = 0.004) but not DSD (p = 0.09) was an independent predictor of the endpoints. Of note, mean 24-hour systolic blood pressure was excluded from the model when SSD was taken into account. In fully adjusted models, the hazard ratio for a 24-hour SSD = > 15 mmHg was 2.0 (95% CI, 1.2–3.4). For coronary events (N = 30), the hazard ratio was 2.8 (95% CI, 1.3–6.1). Conclusions: Short-term BPV evaluated with 24-hour ambulatory monitoring adds to the risk stratification for cardiovascular events in young-to-middle-age subjects screened for stage 1 hypertension with a doubled risk of events for people with SSD = > 15 mmHg.